The effect of financial technology on financial inclusion in Ethiopia during the digital economy era - Mesfin Menza; Wondwossen Jerene; Mubarek Oumer (Cogent Social Sciences)
The digital economy is overwhelming the whole world and expected to help the socio-economic enhancement especially in the developing countries. The banking industry is significantly investing on introducing financial technologies especially in developing countries like Ethiopia ultimately to achieve financial inclusion goals. Hence, this study was aimed to investigate the effect of financial technology (Fintech) for financial inclusion in Ethiopia during this digital economic era. For this purpose, secondary data was collected from nine commercial banks (panel units) from the year 2015 to 2020. The random effect model was applied to estimate the effect of explanatory variables on the variable of interest based on Hausman test results and after testing all possible assumptions of the model. Accordingly, the finding revealed that ATM, mobile banking, POS, and agent banking were found to have statistically significant positive effect on financial inclusion. The authors suggested that increasing the adoption of digital financial technologies (Fintechs) in the rural and urban area would positively contribute for ensuring financial inclusion strategies of policy makers and banking practitioners.